An Annotated Checklist on the Introduced Aquatic Fauna of Two River Systems on Negros and Panay, Philippines - Linaugo, Joji D.; Alcala, Ely L.; Bucol, Abner A.; Menes, Carmen C.; Pacalioga, Jessica O.; Turbanos, Ferdinand M.; Patiluna, Ma. Lotus E. (Silliman Journal, 2022)
This paper presents an annotated list of 16 species of introduced BRVBUJDGBVOBJO#BHP3JWFSJO/FHSPT0DDJEFOUBMBOE+BMBVS3JWFS JO*MPJMPQSPWJODFJOUIF1IJMJQQJOFT&MFWFOTQFDJFTPGmTI UISFF species of herptile, and two species of mollusk are discussed JOUIJTQBQFS5IFiKBOJUPSmTIwPS4PVUI"NFSJDBO4BJMmOBUmTI (Pterygoplichthys disjunctivus), the Zebra Fish (Danio rerio), the Molly (Poecilia sphenops) appear to be new records of introducedspecies in Bago and Jalaur River systems. Introduction of these TQFDJFTBSFNPTUMJLFMZUISPVHIUIFBRVBDVMUVSFQSPKFDUTBOEUIF BRVBSJVNUSBEF